The Influence of Tourist Motivation on Psychological Well-Being at the Curug Gorobog Nature Tourism Destination Sumedang - Ilham Ramdhani; Indra Safari; Gilang Pratama Putra (Indonesian Journal of Tourism and Leisure, 2026)
This study examines the impact of tourist motivation on psychological well-being at Curug Gorobog, a natural tourist destination located in Citengah Village, South Sumedang, Sumedang Regency. Employing a quantitative approach with a survey-based methodology, the research utilized primary data as the principal source of information. Respondents were selected through simple random sampling, specifically targeting individuals who had previously visited Curug Gorobog. The final sample comprised 396 participants. Data analysis was conducted using simple linear regression. The findings indicate that tourist motivation exerts a positive and significant influence on the psychological well-being of visitors at Curug Gorobog. This relationship is substantiated by a t-statistic of 22.802 with a significance level of p < 0.05. Furthermore, the coefficient of determination (R2) of 0.569 suggests that tourist motivation accounts for 56.9% of the variance in psychological well-being, while the remaining 43.1% is attributable to other factors beyond the scope of this study.